Avaliação do gerenciamento de resíduos de serviços de saúde em estabelecimentos da Atenção Básica à Saúde - Mekaro, Karen Sayuri (Universidade Federal de São Carlos, 2019)
This research aimed at evaluating the Medical Waste management in services from Primary Care of São Carlos city, state of São Paulo. This is an exploratory and descriptive study, performed in 22 Family Health Units (FHU) and 12 Basic Health Units (BHU), with participation of 33 contributors (one participant from each health unit as the responsible of medical waste management, one of the individuals presented unavailability to participate in the survey during data collection). Data collection consisted in scaling the medical waste, filling questionnaires with the 33 research individuals and field observation. The data were compiled and analyzed through descriptive statistics. Data collection was initiated after authorization from the Municipal Health Department of São Carlos-SP, approval of the Research Ethics Committee of the Federal University of São Carlos and signing of the Informed Consent Form by the participants in the research. Results: the total HWC generation was 719.665 kg in the 27 healthcare entities, with 300.140 kg of Medical Waste generated by the FHU and 419.525 kg of medical waste from the BHU. It is noticeable that 66.6% (14) of FHU participant did not know how the segregation of chemical residues was performed; 61.8% (13) of FHU participant were not able to report if common wastes were subjected to any kind of treatment; 50.0% (6) of the BHU participants were not able to inform the type of final disposition of the Medical Waste. The daily generation of Medical Waste in Primary Care services was higher than the numbers found in the literature, suggesting possible gaps in the management of Medical Waste, in which the low complexity of the service does not justify the high amount of Medical Waste generated. Those responsible for the Medical Waste of the participating units were all nurses and presented a knowledge that doesn’t comply with the standards about the management of the Medical Waste, compromising all the management of the Medical Waste, and a reorganization of the management is essential to make it environmentally sustainable. The proper handling and management of Medical Waste are related to the public policies build up by management, in order to implement measures of minimization, adequate segregation and selective collection, in addition to activities aimed at training both waste managers and professionals working in these types of services.
Evaluation of medical waste management in primary care centers
Keywords: Resíduos de serviços de saúde; Gerenciamento de resíduos; Saúde ambiental; Saúde pública; Medical waste; Waste management; Environmental health; Public health; CIENCIAS DA SAUDE